Improving Problem Solving Ability of 8th Grade Student through The Problem based Learning Model - Sri Fadila Andesa; Suci Fitriani (Journal of Curriculum and Pedagogic Studies (JCPS), 2022)
Mathematics learning motivation and students' capacity for problem-solving are still below expectations. The majority of students have difficulty with mathematical issues that are presented as word problems and non-routine problems. This study sought to ascertain whether the Problem Based Learning model enhanced students' capacity for problem-solving and learning motivation. This research was a classroom action research (CAR). This CAR focused on the students of SMP N 8 Banda Aceh's capacity for problem solving. Researchers in this study applied the Problem Based Learning model to all of the learning tasks from cycle 1 to cycle The result showed that The learning outcomes of students studying fractions in have improved using Problem Based Learning Model.